Keputusan Masyarakat Dalam Pemilihan Rumah Sakit Untuk Pelayanan Kesehatan Di Wilayah Malang Raya - Ella Mayasari; Nihayatul Munaa; Lailatul Kodriyah; Ida Herawati; Ronal Surya Aditya (Jurnal Keperawatan, 2020)
Hospital is one of the public facilities used by the Indonesian people in the health sector. A hospital is a health service institution that conducts complete individual health services that provide inpatient, outpatient and emergency services. This research was conducted descriptively Qualitative research using a phenomenological approach was conducted in November 25 to 29 November 2019. data were obtained through in-depth interviews. Stages of analysis Data obtained by in-depth interviews can be analyzed the process of data analysis with Interpretative Phenomenological Analysis (IPA). The population of this study was 11 respondents. The method of selecting participants was carried out using a purposive sampling technique. Age of respondents 25-50 years. The results found 7 themes, namely: Distance, BPJS Class, Rates, services, Doctors, Diseases, Facilities. Conclusion: In Hospital Selection the distance is a major factor in the selection of Hospitals. The next factor is BPJS or health insurance which is owned by each individual in the selection of hospitals because it will be related to tariffs. hospitals that affect the expenditure of individuals who are sick.